Active edible packaging based on milk proteins: A route to carry and deliver nutraceuticals. (May 2021) - Daniloski, Davor; Petkoska, Anka Trajkovska; Lee, Nanju A.; Bekhit, Alaa El-Din; Carne, Alan; Vaskoska, Rozita; Vasiljevic, Todor
Abstract: Background: Environmental awareness and consumer demand for healthy diets and wellness have directed the attention of academia and the food industry towards discovering sustainable packaging materials, including active edible type of packaging. Numerous active edible films and coatings use milk proteins in their formulations. Milk proteins, comprising of caseins and whey proteins, are important for human nutrition, but also gain importance as natural product polymers with potential to be used as encapsulation carriers for nutraceuticals for various food and biotechnological applications. Scope and approach: This review provides an overview of the recent trends and advances in active edible packaging materials originating from milk proteins and their technological characteristics (delaying moisture loss, providing oxygen barriers, exhibiting good tensile strength and elongation, offering flexibility, and generally having neutral taste and flavour). Recently, significant achievements have been made to increase the shelf life of perishable food and control the release and transport of nutraceuticals and bioactive molecules by using milk proteins. The results presented here show that packaging materials comprised of milk proteins can be optimised by the food industry and be employed as active edible packaging for improved quality and safety features of fresh food products. Key findings and conclusions: Active edible packaging materials made from milk proteins provide great potential for improving food safety, quality and versatility, and could potentially decrease the number of concerns from suppliers and consumers. Nevertheless, certain critical aspects, such as regulatory issues (migration of active substances, labelling, and allergenicity), economics and customer desires, should be considered for the successful introduction of active edible packaging solutions in the food sector. It is to be expected that the milk protein-based vehicle systems present alone or as part of novel sustainable packaging forms will become an essential strategy for launching safe food products, and therefore have the potential for increasing profit margins for the food industry. Graphical abstract: Image 1 Highlights: Milk protein based functional edible packaging is reviewed. Film forming properties of caseins and whey proteins are presented. Edible films made from milk proteins have several advantages over synthetic polymers. Active edible packaging from milk proteins shows a promising ability for nutraceuticals' encapsulation and delivery.